2011
DOI: 10.1017/jfm.2011.93
|View full text |Cite
|
Sign up to set email alerts
|

Polar confinement of the Sun's interior magnetic field by laminar magnetostrophic flow

Abstract: The global-scale interior magnetic field Bi needed to account for the Sun's observed differential rotation can be effective only if confined below the convection zone in all latitudes including, most critically, the polar caps. Axisymmetric solutions are obtained to the nonlinear magnetohydrodynamic equations showing that such polar confinement can be brought about by a very weak downwelling flow U ~ 10−5cms−1 over each pole. Such downwelling is consistent with the helioseismic evidence. All three components o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 37 publications
3
21
0
Order By: Relevance
“…The polar field cases presented in Section 3.2 closely resemble the axisymmetric polar model of Wood & McIntyre (2011). The magnetic field is confined by the downwelling meridional flow in the tachocline, whose penetration depth into the radiation zone depends on the strength of the magnetic field.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…The polar field cases presented in Section 3.2 closely resemble the axisymmetric polar model of Wood & McIntyre (2011). The magnetic field is confined by the downwelling meridional flow in the tachocline, whose penetration depth into the radiation zone depends on the strength of the magnetic field.…”
mentioning
confidence: 84%
“…On this basis, Gough & McIntyre argued that the polar magnetic field can only be confined by meridional flows that downwell in the tachocline and hold the field in an essentially laminar advection-diffusion balance. Such downwelling meridional flows are, in fact, expected in the high-latitude tachocline, as a result of "gyroscopic pumping" by the retrograde rotation of the overlying convection zone (Spiegel & Zahn 1992;McIntyre 2000;Wood & McIntyre 2011;Wood & Brummell 2012;Miesch et al 2012). The characteristic velocity of this downwelling, U , say, can be estimated from the observed differential rotation of the tachocline, if we assume that the tachocline is in thermal-wind balance and local thermal equilibrium (Gough & McIntyre 1998;McIntyre 2007, p. 194).…”
Section: The Gough and Mcintyre Modelmentioning
confidence: 99%
“…The turbulence within this layer is believed to play a crucial role in redistributing angular momentum and mixing and yet remains poorly understood (see e.g. Tobias 2005;Wood & McIntyre 2011). Recent investigations using both direct numerical simulations and direct statistical simulations have demonstrated that magnetic fields can strongly affect the dynamics of stably stratified turbulent flows (Tobias, Diamond & Hughes 2007;Tobias, Dagon & Marston 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, being axisymmetric, difficulty was experienced in preventing magnetic field close to the axis of symmetry from penetrating through the tachocline and adding a direct Lorentz coupling between the convection zone and the radiative interior, almost eliminating the polar tachocline shear. This might be regarded as raising a serious problem, notwithstanding the recent demonstration by Wood and McIntyre (2011) of the existence of a steady state with a field wholly confined to the radiative interior. However, gyroscopic pumping inevitably causes an almost horizontal flow in the tachocline away from the poles (and, in the case of the sun, from the equator too) towards the latitudes AE 0 (e.g.…”
Section: Introductionmentioning
confidence: 99%